Myokines derived from contracting skeletal muscle suppress anabolism in MCF7 breast cancer cells by inhibiting mTOR - Davis, Amanda R.; Goodenough, Chelsea G.; Westerlind, Kim C.; Strange, Robert; Deaver, John W.; Ryan, Patrick J.; Riechman, Steven E.; Fluckey, James D. (Frontiers in Physiology, 2022)
There is strong evidence that physical activity has a profound protective effect against multiple types of cancer. Here, we show that this effect may be mediated by factors released from skeletal muscle during simulated exercise, in situ, which suppress canonical anabolic signaling in breast cancer. We report attenuated growth of MCF7 breast cancer cells in the presence of a rodent-derived exercise conditioned perfusate, independent of prior exercise training. This reduction was concomitant with increased levels of DEPTOR protein and reduced mTOR activity.